2016
DOI: 10.1080/19476337.2016.1149226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods on the physical properties of durum wheat pasta

Abstract: The aim of the study was to evaluate the effect of drying methods on the physical properties of pasta. Pasta was processed from durum wheat semolina and dried at low temperature in a drying oven, at very high temperature in a convection-air oven, and under reduced pressure in a vacuumdrier. Pasta after extrusion without drying was referred to as control. Cooking properties, color, and textural properties of the pasta were evaluated. The results show that drying method had a significant impact on the physical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
3
28
1
1
Order By: Relevance
“…The cooking loss value should not exceed 9–10% which is considered the acceptable range for starch noodles (Tan, Li, & Tan, ). The highest cooking loss was observed in infrared‐dried and hot‐air‐dried PEIN (Table ) due to the long drying time and high temperature which denatured the protein as reported by Güler et al () and Piwińska, Wyrwisz, Kurek, and Wierzbicka (). As mentioned earlier, the higher drying rate of microwave drying compared to infrared drying and hot‐air drying resulted in less leached amylose in the matrix (Khir et al, ; Palav & Seetharaman, ) and this was regarded as producing better quality PEIN.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The cooking loss value should not exceed 9–10% which is considered the acceptable range for starch noodles (Tan, Li, & Tan, ). The highest cooking loss was observed in infrared‐dried and hot‐air‐dried PEIN (Table ) due to the long drying time and high temperature which denatured the protein as reported by Güler et al () and Piwińska, Wyrwisz, Kurek, and Wierzbicka (). As mentioned earlier, the higher drying rate of microwave drying compared to infrared drying and hot‐air drying resulted in less leached amylose in the matrix (Khir et al, ; Palav & Seetharaman, ) and this was regarded as producing better quality PEIN.…”
Section: Resultsmentioning
confidence: 63%
“…The maximum distance of infrared‐dried PEIN was significantly higher ( p ≤ .05) than for the hot‐air‐dried PEIN due to the high temperature (above 100 °C) promoting cross‐linking of the two gluten proteins (glutenin and gliadin) through disulfide bonds. It further entrapped starch granules, leading to a continuous matrix and developed a stronger protein network than from drying at a lower temperature (Mercier et al, ; Ogawa, Chuma, Aimoto, & Adachi, ; Piwińska et al, ). This was similar to the work of Mercier et al () who found that high‐temperature drying was associated with a higher breaking strength and distance regarding noodle quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Wójtowicz (2006), pasta hardness depends on the kind of raw material used for its production, higher hardness being characteristic of pastas from the products of milling of durum wheat than of soft wheats. Piwińska et al (2016) demonstrated that pasta hardness is affected by the conditions of the process of drying. In our study, the hardness of dried and ready pastas ranged from 9.4 to 33.3 N and it was statistically differentiated (Tab.…”
Section: 9mentioning
confidence: 99%